Migrant family, school and community in the Equatorial Andes: Permanence and change of cultural identity - Marta Rodríguez Cruz (Íconos)
The relentless impoverishment of the peasant economy has led the indigenous population to resort to emigration as a way to diversify their survival- related risks. However, this has a serious impact in traditional family relationships and in the transmission and subsistence of cultural identity among the young in the communities. The importance of family, school and community as cultural identity transmission agents is taken for granted, but, on the other hand, migration tends to deprive the young from enjoying the benefit of a close father figure while they grow up. Given these facts, the present research aims at two main objectives: a) to find out the consequences of emigration for the reproduction and conservation of cultural patterns among the younger generations, and b) to highlight the role of school and community in preserving traditional forms of identity. Qualitative methods are used, including field observation (participatory and non-participatory), discussion groups, semi-structured interviews and informal conversations. Findings show that the community plays a very important part in preserving cultural identity, in spite of the weakening of the nuclear family and of the fact that the school system is not geared to preserving and protecting indigenous culture. The article concludes that there are not two, but three institutions that are crucial for the reproduction of indigenous ethnic identity: family, school and community.